The level of conceptual change in science learning progress based on local wisdom among prospective elementary school teachers - Susanna Vonny Noviana Rante; I Ketut Linggih; Yeral Baso’; Marvita I. Pilo; Delina A. La’Bi’; Markus Deli Girik Allo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to evaluate the conceptual change of prospective elementary school teachers after participating in science learning based on local wisdom using Conceptual Change Texts. The research employed a descriptive quantitative method involving 30 Primary School Teacher Education students from Universitas Kristen Indonesia Toraja enrolled in the Basic Science Concepts course. The level of conceptual change was identified through a four-tier diagnostic test and assessments in the Student Worksheet, following established guidelines for determining levels of conceptual change. The results showed that approximately 12.97% of students were at the level of Initial Scientific Conception (ISC), 6.98% at the Static (S) level, 77.18% at the Reconstruction (R) level, 4.01% at the Construction (C) level, and none at the Disorientation (D) level. This study demonstrates that science learning based on local wisdom, using conceptual change texts, effectively minimises misconceptions and leads students to achieve conceptual change at the construction and reconstruction levels.